Phalaropus fulicarius - Boano, Giovanni; Belemsobgo, Urbain; Silvano, Fabrizio; Hema, Emmanuel M.; Belemsobgo, Aristide; Dimobe, Kangbéni; Pavia, Marco (Zenodo, 2022)
Phalaropus fulicarius (Linnaeus, 1758) LITERATURE. — Pavia et al. (2012); Borrow & Demey (2014), STATUS. — Palaearctic vagrant. REMARK. — First record of the species for Burkina Faso documented by Pavia et al. (2012) at Moussodougou Lake, Cascade Region, 16.II.2010. Published as part of Boano, Giovanni, Belemsobgo, Urbain, Silvano, Fabrizio, Hema, Emmanuel M., Belemsobgo, Aristide, Dimobe, Kangbéni & Pavia, Marco, 2022, An annotated checklist of the birds of Burkina Faso, pp. 27-107 in Zoosystema 44 (2) on page 52, DOI:10.5252/zoosystema2022v44a2, http://zenodo.org/record/5999691